On the relationship of accounting information value and stock prices: The moderation of accounting conservatism - Margareta Chaslim (Jurnal Ekonomi Perusahaan, 2021)
The information content of published financial statements has value relevance if it is able to revise investor confidence. The indication is the market reaction in the form of changes in stock prices. Many believe that recently the value relevance of accounting information has declined amid increasing conservatism practices. This research has two objectives. First, detecting the existence of value relevance of accounting information through its effect on changes in the same price. Second, examine the effect of accounting conservatism practices on value relevance. The objects of research are manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2016. The sample size is 320 observations, consisting of 80 companies each year. By using multiple regression as an analytical tool, this study finds that accounting information is proven to have value relevance to stock prices. Accounting conservatism has a different effect on each accounting information.